AB1019 The Detection of Microcirculation Disturbances in Both Hands of Patients with Systemic Sclerosis Using Fluorescence Optical Imaging. (10th June 2014) - Friedrich, S.; Riemekasten, S.; Werner, S.; Schmittat, G.; Burmester, G.-R.; Riemekasten, G.; Ohrndorf, S.; Backhaus, M.
Abstract : Background: Indocyanine green-enhanced (ICG) fluorescence optical imaging (FOI) is a novel imaging method for the detection of inflammation in both hands of patients with arthritis [1, 2]. Patients with systemic sclerosis (SSC) suffer from an impaired microcirculation (Raynaud phenomenon) with the risk of digital ulcers. Objectives: To present microcirculatory disturbances identified by FOI. To this end, distribution patterns of ICG in patients with SSC in comparison to healthy subjects were analyzed. Methods: N=79 subjects (n=53 patients with SSC and n=26 healthy subjects) were included. All participants received FOI examination following the Xiralite-System guidelines (ICG 0.1mg/kg BW i.v.; 6 minute duration). The PrimaVistaMode and the 360s long clip mode (one frame per second) were analyzed. Results: FOI detects the distribution of ICG in the tissue of both hands. After a first strong signal enhancement in the fingertips, the coloring agent usually spreads to the proximal parts of the fingers and hands. Some typical changes in the distribution patterns in SSC were defined as demarcated areas of high ICG-signals ("islands") in the early phase. We detected those "islands" in 58% of patients with SSC and in 23% of healthy subjects (p=0.0004). To find evidence for a reduced acral perfusion, we examined whether the first strong signal enhancement reached the tip of each finger or not. This was apparent in 73% of the healthy subjects and in 33% of the patients with SSC (p=0.0016). A complete disruption of digital microcirculation was defined as lack of an appropriate signal in the distal part of the finger during the whole time of the examination. This was found in 19% of patients with SSC, but in none of the healthy subjects (p=0.026). Conclusions: The FOI-findings show a distinctive scleroderma-pattern: circumscribed ICG-accumulations ("islands") in different regions of the hands early in the examination and initial digital ICG-enhancement proximal of the fingertips. This could be a result of microvascular damage due to SSC as it was significantly more often detected in SSC patients compared to healthy subjects. References: Werner SG et al. Ann Rheum Dis. 2012;71:504-10. Werner SG et al. Arthritis Rheum. 2013;65:3036-44 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3349